Materials for microfabricated implantable devices: a review. Issue 22 (23rd September 2015) - Scholten, Kee; Meng, Ellis
Abstract : A review of microfabricated implantable devices that examines the critical role of material choice in design and fabrication. Abstract : The application of microfabrication to the development of biomedical implants has produced a new generation of miniaturized technology for assisting treatment and research. Microfabricated implantable devices (μID) are an increasingly important tool, and the development of new μIDs is a rapidly growing field that requires new microtechnologies able to safely and accurately function in vivo . Here, we present a review of μID research that examines the critical role of material choice in design and fabrication. Materials commonly used for μID production are identified and presented along with their relevant physical properties and a survey of the state-of-the-art in μID development. The consequence of material choice as it pertains to microfabrication and biocompatibility is discussed in detail with a particular focus on the divide between hard, rigid materials and soft, pliable polymers.